CULINARY JOURNEY OF SELF-DISCOVERY AND EMPOWERMENT IN RATATOUILLE - Alex, Jolly (ShodhGyan-NU: Journal of Literature and Culture Studies, 2026)
Ratatouille(2007) an animated movie is a nuanced exploration of the trans-formative power of art through resistance and self-belief. Its basic premise is about a rat who is blessed with an astute smell of taste and extra-ordinary passion for cooking who eventually emerges as the greatest chef in France. He challenges the stereotypical notion that only humans can cook and proves by his culinary expertise that one can transcend restricting power structures and chase one’s dreams and inspire others too to do likewise. The film is a tribute to pioneers who have been marginalised and alienated yet have dismantled oppressive structures, re-ordered power politics and sparked progressive ideological changes and validated their dreams. The protagonist Remy,illustrates the tension between submission and subversion and the choice to be a loner and move ahead towards uncharted territories and thereby realisation of one’s dreams.The empowerment which springs from self-belief and steadfast pursuit of one’s calling despite opposition-brings forth unprecedented outcomes which are ground-breaking and breath-taking as well. The film underscores the ethical as well as creative dimension of a collaborative approach between human and non-human agents emphasising that true talent can arise from anywhere,literally from the sewers. Hence, the movie is a culinary journey that challenges essentialist norms through a post-structuralist framework affirming empowerment transcending stereotypical constraints.